2016
DOI: 10.1111/ans.13833
|View full text |Cite
|
Sign up to set email alerts
|

One‐stop thyroid nodule clinic with same‐day fine‐needle aspiration cytology improves efficiency of care

Abstract: Surgeon-performed US-FNAC decreases the time from fine-needle aspiration request to definitive plan and reduces the number of patient visits, providing more efficient care. Patients referred to the endocrine surgery clinic with thyroid nodules have thyroid cancer more frequently than patients referred to radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Additionally, the anticipated surgeon remains fully engaged in the care of the patient from the initial examination through the postoperative period without the likelihood of sacrifi cing quality of care or treatment results. Consistent with this latter suggestion are the results reported by Patel and his associates [12]. They discovered that when the surgeon him or herself performed the thyroid FNAC with US there was a notable decrease in the time to diagnosis and treatment in over 100 cases, which in the fi nal analysis translated into signifi cantly fewer offi ce visits and more effi cient patient care.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, the anticipated surgeon remains fully engaged in the care of the patient from the initial examination through the postoperative period without the likelihood of sacrifi cing quality of care or treatment results. Consistent with this latter suggestion are the results reported by Patel and his associates [12]. They discovered that when the surgeon him or herself performed the thyroid FNAC with US there was a notable decrease in the time to diagnosis and treatment in over 100 cases, which in the fi nal analysis translated into signifi cantly fewer offi ce visits and more effi cient patient care.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, for patients who needed a diagnostic ultrasound once in the clinical pathway, the median time for diagnosis was 166 days. A few other studies compared the timeliness of care of surgeon-performed UG-FNAC vs. radiologist-performed UG-FNAC in patients with thyroid nodules [ 24 , 25 , 26 ]. These studies only evaluated the period from puncture to diagnosis and reported a shorter delay in the first group as well as a reduction in costs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, adjuvant therapy decisions post thyroidectomy are made in the context of a MDT meeting, which was first implemented in 2009 . Along with the published guidelines, and the expertise offered by this multi‐disciplinary group, carefully‐considered decisions are made regarding thyroid cancer treatment; both surgical (completion thyroidectomy, lymph node dissection) and non‐surgical (TSH suppression, RAI use).…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, adjuvant therapy decisions post thyroidectomy are made in the context of a MDT meeting, which was first implemented in 2009. 18,19 Along with the published guidelines, and the expertise offered by this multi-disciplinary group, carefullyconsidered decisions are made regarding thyroid cancer treatment; both surgical (completion thyroidectomy, lymph node dissection) and non-surgical (TSH suppression, RAI use). This approach has also led to our adherence to guidelines, as has been reported by Moore et al in New York, where a similar change in RAI usage was reported following publication of the 2009 guidelines, with management decisions made within a multi-disciplinary environment.…”
Section: Discussionmentioning
confidence: 99%